Deep Learning for Human Action Recognition – Survey - Kiruba, K; Elizabeth, D. Shiloah; Raj, C Sunil Retmin (International Journal of Computer Sciences and Engineering, 2025)
Human action recognition (HAR) in visual data has become one of the attractive research area in the field of computer vision including object detection, recognition, retrieval, domain adaptation, transfer learning, segmentation etc. Over the last decade, HAR evolved from heuristic hand crafted feature to systematic feature learning namely deep feature learning. Deep feature learning can automatically learn feature from the raw inputs. Deep learning algorithms, especially Convolutional Neural Network (CNN), have rapidly become a methodology of choice for analysing recognition of videos. In this paper, details of recent trends and approaches of deep learning including CNN, Recursive Neural Network (RNN), Long Short term Memory (LSTM) and Autoencoders which are used in HAR are discussed. The challenges are identified to motivate the researchers for future works